UKRAINIAN TALE: MORAL AND AESTHETIC PARADIGM OF FOLKLORE AND LITERATURE - Riazanova, V. A.; Zayats, O. T.; Ignatolia, A. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The present article deals with the concepts of Ukrainian literary fairy tale and morality. Evolutionary stages of development of the Ukrainian literary fairy tale, components of moral development and levels of moral consciousness are considered. The specificity of fairy tales is found out within the limits of the unique direction of the artistic phenomenon at the level of modern knowledge of fairy-tales. The ideas of moral and aesthetic education of children are systematized on the basis of Ukrainian folklore and literary studies. Moral qualities of the person which are formed by means of inclusion of the fairy tale are defined in process of education. The place and role of the Ukrainian literary fairy tales in the process of education of moral and aesthetic qualities of children is outlined. The principles of transformation of folklore material and features of its assimilation by literature are considered. The opinions of many famous scientists and teachers on the use of folklore in the education of children are analyzed. It is determined that the Ukrainian literary fairy tale contains a considerable reserve of creativity for working with children, as well as developing their morality. It teaches children common to mankind values, thus forming a character trait such as self-esteem. The fairy tale prepares a child for a future life in the real world and shows examples of overcoming difficulties. It forms the moral qualities that will remain with the child for life. With the help of a fairy tale, the child develops moral and aesthetic feelings. Her potential includes a source of morality and at the same time is a popular means of upbringing. It promotes the formation of certain values, an ideal. The ideal for a child is a long-term perspective, which one she will strive, checking her affairs and deeds with her. An ideal, acquired in childhood, will in many ways define it as a person. It is concluded that the effectiveness of using the Ukrainian literary fairy tale in the moral and aesthetic education of children is verified in practice and very productive.